Bałuty in the 21st century. Identity crisis? - Antonina Łukowska, Maria (Koszty współczesnych kryzysów, 2021)
The aim of the study is to present a certain cultural phenomenon, which is the Bałuty district of Łódź, a district similar to other working-class suburban districts of cities in the world and in Europe. This cultural phenomenon consists in their persistence despite numerous, five crises, and even in the gradual extension of the term “Bałuty” after each of them beyond the administrative boundaries of this district. Using an ethnoscience approach which assumes that culture is not a material phenomenon, does not consist of things, people, behaviors or feelings, but is an organization of all these components, a form of what people store in their mind, their models of perception, association and interpretation of the world, methods enabling learning the grammar of Bałut culture from the point of emic anthropology were used. Both existing etic sources (historical and anthropological studies) and induced emic sources (interviews, memories, photographs, published and unpublished) were used for this purpose. Attempts were made to present this grammar of Bałut culture as a cultural fact of long duration through the history of the district as a village, suburb and city within a city, the characteristics of its inhabitants, a description of five crises related to the attack on Bałut’s cultural identity and the strategy of its preservation, e.g. The specificity of language and narrative, the most important spaces for the district (Bałucki Rynek, “Limanka”) and the contemporary struggle to preserve cultural identity in the era of pandemic and lock down. The need for further, in-depth research on specific issues related to the culture of this district was also highlighted, which have not yet received separate studies.